2017
DOI: 10.1038/mp.2017.77
|View full text |Cite
|
Sign up to set email alerts
|

Largest GWAS of PTSD (N=20 070) yields genetic overlap with schizophrenia and sex differences in heritability

Abstract: The Psychiatric Genomics Consortium-Posttraumatic Stress Disorder group (PGC-PTSD) combined genome-wide case–control molecular genetic data across 11 multiethnic studies to quantify PTSD heritability, to examine potential shared genetic risk with schizophrenia, bipolar disorder, and major depressive disorder and to identify risk loci for PTSD. Examining 20 730 individuals, we report a molecular genetics-based heritability estimate (h2SNP) for European-American females of 29% that is similar to h2SNP for schizo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
339
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 381 publications
(355 citation statements)
references
References 55 publications
12
339
0
4
Order By: Relevance
“…rs406001) were identified in a previous GWAS of post-traumatic stress disorder (PTSD), but not replicated in the original GWAS 40 . Furthermore, this locus was only nominally associated with PTSD in a much larger GWAS 41 . This, coupled with the low minor allele frequency of SNPs in the genome-wide significant locus in our GWAS, suggests that this may be a chance finding, rather than an effect of PTSD on participation.…”
Section: Discussionmentioning
confidence: 60%
“…rs406001) were identified in a previous GWAS of post-traumatic stress disorder (PTSD), but not replicated in the original GWAS 40 . Furthermore, this locus was only nominally associated with PTSD in a much larger GWAS 41 . This, coupled with the low minor allele frequency of SNPs in the genome-wide significant locus in our GWAS, suggests that this may be a chance finding, rather than an effect of PTSD on participation.…”
Section: Discussionmentioning
confidence: 60%
“…Sex has been shown to influence the likelihood of a PTSD diagnosis, and preliminary work suggested that these genetic influences were stronger in women than men [29]. However, other works on BDNF by sex interactions to predict related phenotypes have mixed results [46, 47].…”
Section: Discussionmentioning
confidence: 99%
“…However, a major limitation in the extant literature is that potential ethnicity and sex differences were not examined. Examination of sex effects is critical, considering the finding that PTSD may be more genetically driven in females [29]. To illustrate, preliminary evidence has shown that estrogen induces the synthesis of BDNF in several brain regions [30], which could contribute to an elevated risk for PTSD in females versus males.…”
Section: Introductionmentioning
confidence: 99%
“…The Psychiatric Genomics Consortium (PGC)-PTSD working group has been leading efforts to identify genetic risk variants associated with PTSD (Logue et al , 2015), and the first meta-analysis of PTSD GWASs ( N =20,070) has been recently completed by this group (Duncan et al , 2017). In the present study, we used summary statistics from the PGC-PTSD meta-analysis of Duncan and colleagues (2017) to conduct the first GWAS-based investigation of potential genetic overlap between PTSD and cardiometabolic traits.…”
mentioning
confidence: 99%
“…In the present study, we used summary statistics from the PGC-PTSD meta-analysis of Duncan and colleagues (2017) to conduct the first GWAS-based investigation of potential genetic overlap between PTSD and cardiometabolic traits.…”
mentioning
confidence: 99%